Minimizing the creep of recycled polypropylene/rubberwood flour composites with mixture design experiments - Ratanawilai, Thanate (Journal of Composite Materials, 2014)
Composites of rubberwood flour (RWF) and recycled polypropylene (rPP) were produced into panel samples by using a twin-screw extruder. The effects on creep behavior of mixture fractions of rPP, RWF, maleic anhydride-grafted polypropylene (MAPP), and ultraviolet (UV) stabilizer were studied in a D-optimal mixture design. Creep was significantly affected by the composition. Increasing the fraction of RWF decreased creep, while MAPP and UV stabilizer increased it. The models fitted were used to optimize a desirability score that balanced multiple creep characteristics. The modelbased optimal formulation 50.5 wt% rPP, 44.9 wt% RWF, 3.5 wt% MAPP, 0.1 wt% UV stabilizer, and 1.0 wt% lubricant was experimentally validated to have low creep closely matching the model predictions.